A concept of regulating the distribution of continuous brittle phases by spatial division of the Ti3SiC2/Ti2AlNb brazing seam. (September 2022) - Zhang, Bo; Chang, Qing; Sun, Zhan; Li, Degang; Pan, Hui; Zhang, Lixia
Graphical abstract: Highlights: A novel concept was proposed by spatially dividing the brazing seam to regulate continuous brittle phases. Inserting a Cu foam into the Ti3 SiC2 /Ti2 AlNb brazed joint could disperse the TiCuSi intermetallic that should have been continuous. The maximum shear strength of the Ti3 SiC2 /Ti2 AlNb brazed joint was improved by 76% under the contribution of Cu foam. The brazing seam with the dispersive brittle TiCuSi intermetallic surrounded by ductile matrix has superior resistance to cracking. Abstract: Herein, a novel concept was proposed to address the issue that continuous brittle phases degrade the mechanical properties of a brazed joint. In this concept, the continuous brittle phases could become dispersive by inserting a network-like structure to divide the brazing seam spatially. This concept was verified in a specific brazing system, where Ti3 SiC2 ceramic and Ti2 AlNb alloy were brazed by an AgCu interlayer. Ductile Cu foam with a network-like structure was used to disperse the continuous brittle TiCuSi intermetallic that should have in-situ formed in the Ti3 SiC2 /AgCu/Ti2 AlNb brazed joint. Results show that the effect of Cu foam on dispersing the brittle TiCuSi intermetallic is pronounced. The effects of holding time and pore size on the dispersion effect of Cu foam were investigated. The joint fracture analysis and micro-mechanical properties of phases analysis reveal that the dispersive TiCuSi intermetallic is superior to the continuous one. The reason is that the microstructure of discrete TiCuSi intermetallic surrounded by ductile Ag-based and Cu-based solid solutions has a more robust capacity to accommodate microcracks. Thus the brazed joint is toughened and strengthened.